From Savage to Sublime (And Partway Back): Indians and Antiquity in Early Nineteenth-Century American Literature - Mark Niemeyer (Transatlantica)
This article examines the comparisons made between Indians and Antiquity in early nineteenth-century American literature (notably in the works of Washington Irving and James Fenimore Cooper); to do so, it begins by reaching back to references in European and American writings of the eighteenth century. One of the main motivations behind the associations between Native Americans and the Ancient World made in the early decades of the nineteenth century was to “elevate” Indians in order to transform them into worthy symbols of the recently established United States. Such associations also rendered them suitable subjects for treatment by authors inspired to a large extent by the Romantic Movement and involved in the project of creating a national literature for the new country. Bringing together these two quite different worlds, however, resulted in various ambiguities: it simultaneously reinforced the suggestion that Indians were already part of the past (providing a certain complicity with the continuing destruction of Indian culture) and questioned the then dominant image of Ancient Greece and Rome as examples of some of the highest levels attainable of government and human civilization.